Pertentangan Prosedural Antara Talak Lisan Dan Hukum Formal: Kajian Yuridis Terhadap Perlindungan Hak Perempuan Dalam Kasus Perceraian Di Kota Probolinggo - Ah Fathan Azhari; Ahmad Syaifuddin Romli (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The practice of talak lisan (oral divorce) outside the court remains prevalent across various regions in Indonesia, including Probolinggo City, and poses serious challenges to the protection of women’s rights following divorce. This phenomenon contradicts Indonesia’s positive legal framework, which mandates that all forms of divorce must be authorized through court proceedings to ensure legal certainty and substantive justice, particularly for the affected women. This study aims to analyze the procedural conflict between oral divorce practices and the formal legal system, as well as their implications on the legal status and rights protection of women who experience divorce without judicial endorsement. A qualitative approach was employed, using a case study strategy and a normative-juridical method enriched with empirical data gathered through semi-structured interviews and document analysis. The findings reveal that oral divorce practices are often legitimized by socio-religious norms and the authoritative role of religious figures, yet they fail to provide legal safeguards concerning spousal maintenance, child custody, and civil status. This procedural disparity weakens women's legal standing and highlights a critical gap in the implementation of gender justice and legal certainty within Indonesia’s Islamic family law system. The study offers both conceptual and practical contributions toward reforming Islamic family law to be more responsive to social realities and the need for legal protection of women, and it advocates for greater harmonization between religious law and state law within the family justice system.